PERAN GURU PENDIDIKAN AGAMA ISLAM DAN BIMBINGAN KONSELING DALAM MENANGANI KASUS BULLYING - Agistia Sari; Eneng Muslihah (Program Studi Pendidikan Agama Islam Program Pascasarjana Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2020)
This study aims to explain the role of PAI and BK teachers in handling bullying cases that occurred in SMK Negeri 2 and SMK Negeri 4 Kota Serang, the factors that cause, shape, impact, and case resolution. The research approach is descriptive qualitative with data collection techniques, observation, interviews and documentation. The subjects of this study consisted of 2 PAI teachers, 2 BK teachers, 2 vice principal students, 2 school principals, and 20 students. The research subjects consisted of class X, XI, and XII who were taken randomly. The research was conducted from January to February 2020, at SMK Negeri 2 and SMK Negeri 4 Kota Serang, Banten Province. The results of the study (1) Perceptions of Islamic Religious Education Teachers and Counseling Guidance about bullying, namely immoral behavior; 2) Students' perceptions and experiences about bullying are considered as jokes or jokes, while the experience of bullying in vocational school students is in the form of threats, in the form of challenges to prove their masculinity by fighting; 3) forms of bullying, namely verbal and non-verbal; 4) The causes of bullying are a sense of seniority, a feeling of wanting to be respected and feeling that they will not be defeated by anyone; 5) The impact of bullying, namely psychological trauma, reluctance to go to school, fear, lack of confidence; 6) Forms of solving Bullying cases in the form of summons, data collection, coordination, mediation, and sanctions; 7) Efforts to prevent bullying cases, namely discussing and providing classical understanding; 8) The role of the PAI teacher is to provide religious spiritual advice; 9) The role of the guidance and counseling teacher is to collect data and coordinate with related stakeholders; 10) The different approaches to handling PAI teachers are psycho-spiritual in nature, while BK teachers are psychopedagogic.